Repetition in class of FLE: correction, evaluation, and transmission of knowledge - AFRI, Maya Ines (Journal of Human Sciences, 2022)
Our reflection is oriented towards the analysis of repetition activity in FFL class. This technique, which seems inert, is, however often favoured by its producers in all areas of life, especially in language classes. Is it just a way of picking up on that? Where does it go beyond that? through this practice, the teacher facilitate the understanding between the class participants, correct their erroneous statements, evaluate them and transmits new knowledge. Learners repeat to self-correct, help each other and assert themselves as subjects. An analysis of the repetitions in two third year average courses recorded and transcribed has been done, in order to show the contribution of these productions on the management of communication in the classroom on the one hand, and on the teaching of learning French as a foreign language on the other.